NON-STANDARD TASKS AS A MEANS OF ACTIVATION ACTIONS OF JUNIOR SCHOOLCHILDREN - Z.V. Druz; B.H. Druz (Academy of Cognitive and Natural Sciences, 2004)
The peculiarity of using the utraditional tasks to activate junior pupils studying in innovation teaching technology are examined in the article.